Model Kepemimpinan Efektif dalam Lembaga Pendidikan Islam: Studi Tipe dan Gaya Kepemimpinan - Rahmawati, Aulia; S, Rinny; Asmendri, Asmendri; Sari, Mila (Indo-MathEdu Intellectuals Journal, 2025)
Leadership in Islamic education is a strategic factor in shaping institutional culture and improving the quality of education. This article examines the types and styles of leadership that are relevant in Islamic educational institutions, including autocratic, participatory, laissez-faire, transformative, paternalistic, and militaristic styles. The analysis is based on the principles of the Qur'an and Hadith, with a focus on the values ​​of amanah, justice, sincerity, and responsibility. The results of the study indicate that the application of a contextual leadership style based on Islamic values ​​can strengthen institutional performance and shape the character of students who have good morals. This study recommends the importance of developing Islamic leadership capacity in education to realize the vision of holistic and sustainable Islamic education